Aneurysmal subarachnoid hemorrhage: long-term trends in incidence and survival in Olmsted County, Minnesota - Giordan, Enrico (J Neurosurg, 2020)
INTRODUCTION: Recent population-based and hospital cohort studies have reported decreasing incidence of aneurysmal subarachnoid hemorrhage (aSAH) and declining aSAH-associated case fatality rates. Principal drivers of these trends are debated; however, improvements in smoking cessation and hypertension control may be critical factors. METHODS: The population-based medical records-linkage system of the Rochester Epidemiology Project was used to documented aSAH incidence and 30-day case fatality rates during a 20-year study period, 1996–2016, in Olmsted County, MN. Incidence rates in the study period were compared with data from a previous Olmsted County study about aSAH incidence from 1965 to 1995 and with regional trends in tobacco use. RESULTS: 119 incident cases of aSAH cases were included. The median age at the hemorrhage was 59 (range 16–94) years; 74 were female (65%). The overall average annual aSAH incidence rate was 4.2/100,000 person-years (P-Y). The aSAH incidence rate decreased from 5.7/100,000 in 1996 to 3.5/100,000 P-Y in 2011 – 2016. The overall aSAH-associated 30-day case fatality was 21.9% and declined by approximately 0.5% annually. We observed an accelerated decline in the fatality rate (0.9%/year) from 2006–2016. Smoking among adult Olmsted County residents decreased from 20.4% in 2000 to 9.1% in 2018. CONCLUSIONS: We observed a decline in the incidence of aSAH and 30-day case-fatality rate from 1996–2016, and an accelerated decline from 2006–2016. Our findings confirm and extend the trends reported by prior studies in the same population. The decrease in aSAH in the years studied paralleled a noticeable reduction in the population smoking rates.